Species introductions shift seed dispersal potential more than extinctions across 120 island plant–frugivore communities - Julia H. Heinen; Donald R. Drake; Kim McConkey; Julian P. Hume; Sébastien Albert; Haruko Ando; Cláudia Baider; Peter J. Bellingham; Samuel B. Case; Charles G. Chimera; F. B. Vincent Florens; Evan C. Fricke; et al. (Proceedings of the National Academy of Sciences, 2025)
Oceanic islands are hotspots of both species extinctions and introductions, which led to marked changes in species composition. This may disrupt key ecological interactions, such as animal-mediated seed dispersal, with potential long-term impacts on ecosystem structure and functioning. While some recent studies on individual taxa and islands report functional shifts, there has been no globally comprehensive study of how these changes vary in intensity and direction across islands. Importantly, it remains unclear how changes in traits of animal communities actually translate to ecologically relevant mismatches with native plant species. We report widespread functional remodeling of frugivore communities based on frugivory-specific traits of all native, extinct, and introduced vertebrate frugivores (birds, mammals, reptiles) from 120 islands in 22 archipelagos. There is a trend for taxonomic and functional substitution, mainly of nonvolant terrestrial mammalian omnivores replacing large-gaped flying frugivores, which caused a mismatch between gape size and seed size. This shift in seed dispersal potential risks underestimation in single-taxon studies. Overall, vertebrate introductions outnumbered extinctions both in terms of species (44 vs. 23%) and islands affected (92 vs. 76%). Moreover, introductions have driven stronger shifts in frugivore trait space compared to extinctions. However, the general patterns are modulated by substantial spatial variation and idiosyncratic functional shifts within frugivore communities on some islands. This, coupled with differences in plant seed size distributions, leads to variability in realized functional mismatches among islands. These results emphasize challenges with predicting functional responses to anthropogenic activities, while highlighting that remodeling of ecosystem interactions is a global concern.